Langmuir probe measurement of the bismuth plasma plume formed by an extreme-ultraviolet pulsed laser; Journal of Physics D: Applied Physics; Vol. 47, iss. 40 - Pira P.; Burian T.; Kolpakova A.; Tichy M. Milan; Kudrna P.; Danis S.; Juha L.; Lancok J.; Vysin L.; Civis S.; Zelinger Z.; Kubat P.; et al. (2014, 2014)
Title screen